The Determinants of Individuals Attitudes Towards Preventing Environmental Damage - Benno Torgler; Maria A. Garcia-Vali\~nas (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper investigates empirically the determinants of individuals attitudes towards preventing environmental damage in Spain using data from the World Values Survey and European Values Survey for the periods 1990, 1995 and 1999/2000. Compared to many previous studies, we present a richer set of independent variables and found that strongly neglected variables such as political interest and social capital have a strong impact on individuals preferences to prevent environmental damage. An interesting aspect in our study is the ability to investigate environmental preferences over time. The results show strong differences over time. Finally, using disaggregated data for Spanish regions, we also find significant regional differences.
Keywords: Q26; R22; Z13; I21; 330; Environment; Regional and time preferences; Political interest; Social capital; Umweltschutz; Meinung; Social Capital; Spanien